A new high-pressure structure of SiO2directly converted fromα-quartz under nonhydrostatic compression - Tsuchiya, Taku; Nakagawa, Saito (Journal of physics. Condensed matter, 2022)
High-pressure behavior of SiO2is one of the prototypical subjects in several research areas including condensed matter physics, inorganic chemistry, mineralogy, materials science, and crystallography. Therefore, numerous studies have been performed on the structure evolution of SiO2under pressure. Here, we show a new structure directly converted fromα-quartz under uniaxial compression. Ourab initiocalculations elucidate a simple transition pathway fromα-quartz to the Fe2P-type phase, and an intermediate state with the Li2ZrF6-type structure appears in this structure conversion. Some interesting properties are found on this intermediate state. (1) The Li2ZrF6-type phase is metastable probably due to a volumetric unbalance between the Li and Zr sites but becomes more energetically stable thanα-quartz over ∼12 GPa. (2) It is vibrationally stable at 0 GPa, suggesting that this phase can be recovered down to ambient condition once synthesized. (3) The crystal structures of Li2ZrF6-type SiO2and phase D, one of dense magnesium hydrous silicates, are found identical, suggesting the stabilization of their solid solution under high-P,Tcondition.High-pressure behavior of SiO2is one of the prototypical subjects in several research areas including condensed matter physics, inorganic chemistry, mineralogy, materials science, and crystallography. Therefore, numerous studies have been performed on the structure evolution of SiO2under pressure. Here, we show a new structure directly converted fromα-quartz under uniaxial compression. Ourab initiocalculations elucidate a simple transition pathway fromα-quartz to the Fe2P-type phase, and an intermediate state with the Li2ZrF6-type structure appears in this structure conversion. Some interesting properties are found on this intermediate state. (1) The Li2ZrF6-type phase is metastable probably due to a volumetric unbalance between the Li and Zr sites but becomes more energetically stable thanα-quartz over ∼12 GPa. (2) It is vibrationally stable at 0 GPa, suggesting that this phase can be recovered down to ambient condition once synthesized. (3) The crystal structures of Li2ZrF6-type SiO2and phase D, one of dense magnesium hydrous silicates, are found identical, suggesting the stabilization of their solid solution under high-P,Tcondition.